Positive vs. Negative Understanding of Liberty: Political Implications - Stojadinović, Višnja (Serbian political thought, 2023)
The subject of this paper is the analysis of the political implications of the distinction between positive and negative understanding of liberty. The author first explains the relevance of this topic within the framework of contemporary theoretical and political discussions. The starting point of this paper is Berlin's distinction between the concepts of positive and negative liberty. In the first part of the paper, the author will deal with the implications of this difference regarding the type of socio-political system and political culture. In this sense, the author will try to show that the democratic concept of liberty is positive liberty, while the classical liberal understanding of liberty is negative. In other words, the relationship between positive and negative liberty reflects on the relationship between democracy and liberalism; this relationship implies possible compatibility, but also potential opposition. In the second part of the paper, the author deals with the implications of the difference between the two concepts of liberty concerning distinctive models of democracy. Referring to Riker's thesis, the author's goal is to show how a positive understanding of liberty leads to a populist model of democracy, while on the other hand a negative understanding leads to a liberal model. The difference between these models of democracy is also reflected in the attitude about whether democracy has instrumental or intrinsic value.
Keywords: Berlin; Riker; Positive liberty; Negative liberty; Liberalism; Democracy; Populism